SOME PECULIARITIES OF THE RADIAL GAS DISTRIBUTION IN GALACTIC DISC - Dzyubenko, M. V. (Одеські астрономічні публікації, 2017)
This paper reports on the theoretical investigation of evolution of the Galaxy. The spiral arms and radial gas flows can be considered as some kind of indicators of the dynamical processes in the disc. Investigation the surface density of gas. The velocity profiles of radial gas flows were selected in such a way to have an agreement between the model predictions and observational data. The model with the radial gas flows gives the results that appear to be in the better agreement with the observations. The results of the model predictions differ significantly comparing to the case of the standard Galactic evolutionary model.